2022
DOI: 10.1039/d1cc06480k
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic poly(β-amino ester)s with enhanced gene transfection activity synthesized through intra-molecular cyclization

Abstract: Topological structure plays a critical role in gene delivery of cationic polymers. Cyclic poly(ß-amino ester)s (CPAEs) are successfully synthesized via sequential Michael addition and free radical initiating ring-closure reaction. CPAE...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
(32 reference statements)
0
16
0
Order By: Relevance
“…It should be noted that the condensation ability has been shown to have a critical role in transfection efficiency, which has been studied in several investigations [ 21 , 45 , 46 , 47 ]. On the one hand, the interaction between the polymer and nucleic acid materials is necessary for polyplex formation, protection against enzymatic digestion, and cell entry via adsorptive endocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the condensation ability has been shown to have a critical role in transfection efficiency, which has been studied in several investigations [ 21 , 45 , 46 , 47 ]. On the one hand, the interaction between the polymer and nucleic acid materials is necessary for polyplex formation, protection against enzymatic digestion, and cell entry via adsorptive endocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has demonstrated that polymers with a cyclic structure often display better biocompatibility and DNA encapsulation capabilities than those with a linear or branched structure. 12,14,15 Herein, we report the first successful construction of a series of cyclic poly(β-amino ester)s (CPAEs) with different types of ring structures by regulating the cyclization tendency at different stages of the step-growth polymerization (SGP).…”
Section: ■ Introductionmentioning
confidence: 99%
“…By changing the end-modified groups, the transfection performance can be improved by several magnitude orders. Then in 2016, Wang et al constructed hyperbranched PAE (HPAE) via the facile A2 + B3 + C2 Michael addition strategy with amines and vinyl groups [ 9 , 10 ], which further improved the gene transfection performance of PAE vectors by increasing the optimal terminal group amount [ 9 , 11 , 12 , 13 , 14 ]. Despite years of research on HPAE structural factors, such as molecular weight, branch ratio, and terminal group screening [ 15 , 16 , 17 , 18 ], there is still a long pathway to clinical applications.…”
Section: Introductionmentioning
confidence: 99%